Intelligent Parking System in Cities - Spratek, Tomáš; Soušek, Radovan (Kaunas University of Technology, 2016)
Presently, towns and cities are increasingly challenged by the issue of effective parking. The issue essentially boils down to “where” and “when”. It is about creating an interactive system easily meeting all requirements, uncomplicated, avoiding high purchase costs and system maintenance. The present paper shows a solution ready now for immediate functional deployment.
Inteligentní parkování ve městech
Keywords: traffic; parking; smart city; system; doprava; parkování; inteligentní město; systém